Design of a high efficiency and low power rectifier circuitry for piezoelectric generator - Low, Ivan Kim Teck (2016)
In the modern world, many portable devices are battery operated and would be a hassle to replace the source when its depleted. Many new renewable energy harvesting system technology have been researched to emerge into a battery-less technology for biomedical devices and several portable devices to help improve our daily life. Piezoelectric energy harvesting is one of the possible and popular method that is capable to provide not only sufficient energy but also a sustainable solution to help to keep the environment greener. However, these energy harvesting system requires integrated circuits to interface with each other to provide a proper energy to the load. This report covers the design specification of the piezoelectric harvester, various topologies of the AC-DC rectifier and includes the comparison of the power efficiency various AC-DC rectifier. Besides that, it also illustrates the design of the Asynchronous Buck-Boost DC-DC Converter working in discontinuous conduction mode (DCM) and demonstrates on how the emulated maximum impedance matching is done to extract the maximum power to deliver to the load side. This two integrated circuits are designed and simulated in the advanced integrated circuit technology (Global Foundries 0.18µm). The AC-DC Rectifier achieved a 99.17% of high efficiency while the Buck-Boost DC-DC Converter obtained a 20.67% efficiency. The solution to improve the efficiency is to design a comparator to detect the peak voltage which can operate the DC-DC Converter.